Syd Hoff's Danny and the Dinosaur and the New Puppy - Hale, Bruce; Cutting, David (David A.) (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2015)
When Danny gets a new puppy, he reunites with longtime friend Dinosaur for a fun-filled day of playing fetch and rolling over, dinosaur-style.
Keywords: Dinosaurs -- Juvenile fiction; Dogs -- Juvenile fiction; Friendship -- Juvenile fiction; Dinosaurs -- Fiction; Dogs -- Fiction; Friendship -- Fiction